REPOSITIONING ISLAMIC BANKS AS WAQF NAZHIR FOR STRENGTHENING THE PRODUCTIVE WAQF ECOSYSTEM IN INDONESIA’S HALAL INDUSTRIAL DEVELOPMENT - Rachman, Abdul; Fauziah, Fauziah; Suhana, Suhana; Imansah, Retno Kartini Savitaningrum; Nurjaman, Muhamad Izazi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the repositioning of Islamic banks’ role as nazhir (waqf managers) in strengthening the productive waqf ecosystem to support the development of halal hubs and halal industrial parks as part of the national Islamic economic acceleration strategy. The research employs a qualitative-explorative method using a case study approach focused on Bank Muamalat Indonesia and Bank Syariah Indonesia (BSI), both of which have been officially designated as nazhir under the supervision of the Indonesian Waqf Board (BWI). The findings reveal that the role of Islamic banks as nazhir has not been systematically optimized to support the financing of productive waqf assets oriented toward the development of the halal sector. According to BWI data (2024), of the total waqf asset value amounting to IDR 1,065 trillion, only 4.39% has been utilized productively. Meanwhile, the development of halal industrial zones such as the Modern Halal Valley in Banten and the Bintan Inti Halal Hub in the Riau Archipelago still faces challenges in accessing inclusive sharia-based financing. As financial institutions and nazhir, Islamic banks hold a strategic position in managing waqf funds through mechanisms such as Cash Waqf Linked Sukuk, venture waqf capital, and the Halal Endowment Fund to finance halal industrial infrastructure development. The repositioning of Islamic banks as nazhir requires synergy and integration among Bank Indonesia (BI), the Financial Services Authority (OJK), the Indonesian Waqf Board (BWI), the National Committee for Islamic Economy and Finance (KNEKS), and the National Sharia Council–Indonesian Ulema Council (DSN-MUI) to regulate the governance of Islamic banking as professional nazhir capable of managing high-value economic waqf assets transparently and accountably. This study recommends a digitally-based collaborative model involving Islamic banks, BWI, and halal industry stakeholders to accelerate the realization of national halal hub development based on productive waqf. The policy implication of this research highlights the need to amend regulations in the Islamic Banking Law, the Waqf Law, and other related legal frameworks to enhance the institutional capacity of Islamic banks in fulfilling their socio-productive function.